Quality of graphene on sapphire: long-range order from helium diffraction versus lattice defects from Raman spectroscopy. Issue 25 (23rd February 2016) - Anemone, Gloria; Climent-Pascual, Esteban; Yu, Hak Ki; Al Taleb, Amjad; Jiménez-Villacorta, Felix; Prieto, Carlos; Wodtke, Alec M.; De Andrés, Alicia; Farías, Daniel
Abstract : We report a new method to produce high-quality, transparent graphene/sapphire samples, using Cu as a catalyst. Abstract : We report a new method to produce high-quality, transparent graphene/sapphire samples, using Cu as a catalyst. The starting point is a high-quality graphene layer prepared by CVD on Cu(111)/Al2 O3 . Graphene on sapphire is obtained in situ by evaporation of the Cu film in UHV. He-diffraction, atomic force microscopy (AFM), Raman spectroscopy and optical transmission have been used to assess the quality of graphene in a metal free area. We used helium atom scattering as a sensitive probe of the crystallinity of the graphene on sapphire. The observation of high reflectivity and clear diffraction peaks demonstrates the presence of flat and homogeneous graphene domains over lateral scales of microns, consistent with the AFM results. Surprisingly, putting graphene on sapphire improves the quality of the He-diffraction spectra. Graphene forms a moiré pattern with a (11 × 11) periodicity, aligned with the (1 × 1) sapphire unit cell. The lattice constant of graphene on sapphire is a = (2.44 ± 0.02) Å. The phonon dispersion of the graphene flexural mode has been measured. This allowed the determination of the bending rigidity k = 0.61 ± 0.15 eV, and the graphene–sapphire coupling strength g = (5.8 ± 0.4) × 10 19 N m −3 . The uniformity of the graphene has also been investigated by Raman mapping. Judging by the ratio of the 2D to G peaks, the quality of the graphene is not degraded by Cu removal. The high transparency (80%) measured in the visible range makes this system suitable for many applications that require hybrid properties commonly associated with metals (conductivity) and insulators (transparency). Our study shows that He-diffraction and Raman provide crucial information on quite different, complementary aspects of the same samples.